Efficacy of chocolate milk in facilitating post-workout regeneration of young male skiers - Kürşat Acar; Ahmet Mor; Fatih Karakaş; Muhammet Cenk Birinci; Mustafa Can Eser; Hakkı Mor; Seydi Ahmet Ağaoğlu; Ceyhun Birinci (Turkish Journal of Kinesiology, 2023)
The use of nutritional strategies has become more widespread in recent years. This study investigates the effect of chocolate milk (CM) consumption on the recovery rate of elite male adolescent alpine skiers after intense training. Twelve male elite alpine skiers aged 13-16 years were randomly divided into two groups: chocolate milk (CM; n = 6) and placebo (PLA; n = 6). After exercise, the CM group was given 400 ml (200+200) of chocolate milk, and the PLA group took water (placebo) in the same regimen. Venous blood samples were taken before and 12 hours after drinking the fluids to determine the activity of selected enzymes, insulin, testosterone, glucose, and some minerals. It was observed that in the CM group, serum AST (Pre: 110.33±126.62 U/L vs. Post: 83.17±100.42 U/L) and CK (Pre: 2393.12±2542.22 U/L vs. Post: 1556.33±1401.45 U/L) activity, as well as testosterone (Pre: 21.12±3.59 ng/mL vs. Post: 15.19±4.96 ng/mL; p=0.028) and iron (Pre: 163.00±14.76 µg/dL vs. Post: 109.00±23.91 µg/dL; p=0.028), decreased significantly, but potassium (Pre: 4.38±0.16 mmol/L vs. Post: 4.64±0.09 mmol/L) and magnesium (Pre: 1.82±0.09 mg/dL vs. Post: 2.07±0.04 mg/dL) levels increased after supplementation compared to baseline levels (p